Role of some legumes in the restoration of burned forest areas - Lombardi P.; Staglianò N.; Talamucci P. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
In order to obtain a preliminary evaluation of the possibility and the modality of restoration of burned forest areas in Mediterranean environments of Tuscany, a trial was carried out in a hilly area near Lucca (Northern Tuscany), just after a wild fire. The trial consisted, after a preliminary evaluation of spontaneous woody and herbaceous vegetation, in the sowing, on a slope, of two forage crops: a mixture of Trifolium subterraneum (cv 'Seaton Park') and T. brachycalycinum (cv 'Clare') and sulla in pure stand (Hedysarum coronarium, ecotype 'Nugola'); the sown cover crops were compared also to development of spontaneous canopy. Observations concerned collected data regarding establishment, soil coverage, canopy structure, litter and recolonization of woody and herbaceous species. The mixture of subclover was more successful than sulla.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)